Entre a revolução e a colaboração : o que uma leitura psicanalítica do laço social aponta para a demanda de reparação do conflito armado colombiano - Omar David Moreno Cárdenas (2019)
The dissertation aimed to understand the meaning of the demand for reparation that is attributed to demobilized members of the FARC (Revolutionary Armed Forces of Colombia) in the context of the end of the armed conflict. To dialogue with the social phenomenon, a historical, political and subjective reading of the Colombian armed conflict was prepared, taking as a reference the Lacanian theory and references of history and political philosophy. The main frame of reference was the psychoanalytic theory with Lacanian orientation, so it was necessary to develop a reflection on the theoretical-clinical implications and the subjective resonances of the notion of "reparation", which comes from the law sciences, interlacing it with the notion of damage, every reparation is preceded by a damage. Two cases were prepared, based on interviews with two demobilized members of the aforementioned group who are serving a sentence in a traditional prison in Cali (Colombia). The cases allowed to open the theoretical-clinical reflection and demanded to build a knowledge on the experience in the armed conflict from two fundamental axes. The first one questions the way the entrance into the armed group takes place, understanding that moment as a paradigmatic fact that subjectively marks the experience of the members of the group and that facilitates some more or less stable subjective moorings. That was called the FARC group function in adolescence. The second axis takes up the constitution of the social bond with respect to the group, finding that the protagonism of one of the modes of discourse, proposed by the Lacanian theory, indicates fundamental particularities in the processes of entry, permanence and output from the armed conflict, mainly thinking about what happens when the hysterical discourse or the discourse of the contemporary master are at the command.